Analisis Strategi Guru dalam Meningkatkan Keterampilan Kolaboratif Siswa Kelas VII di SMP Negeri 1 Kota Baru - Ahmad Prayogo (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study examines the strategies used by teachers to enhance the collaborative skills of seventh-grade students at SMP Negeri 1 Kota Baru. Using a qualitative descriptive approach, data was collected through observations, interviews, and documentation. The findings reveal that teachers implemented strategies such as project-based learning, group discussions, and role-playing to foster collaborative skills. These strategies improved students’ abilities to communicate effectively, share ideas, resolve conflicts, and work as a team. Challenges encountered include unequal participation among students and limited time allocation for collaborative activities. The results highlight the importance of structured teacher interventions and adequate preparation to maximize the benefits of collaborative learning.